WORKPLACE DEVIANT BEHAVIOUR OF HEALTHCARE WORKERS IN ISLAMIC HOSPITAL - Budiman, Budiman; Ardianty, Septi; Wigati, Indah; Baharudin, Baharudin; Abdul Aziz, Siti Fardaniah (Psikis : Jurnal Psikologi Islami, 2022)
Workplace Deviant Behavior has a negative impact on the accomplishment of organizational goals, creates social and economic losses, as well as interferes with a person's safety at work. This study aimed to determine whether Islamic personality and workplace spirituality had any direct effects on work-deviant behavior. Workplace spirituality was also put to the test as a mediator at the same time. Islamic personality was assessed using the Ummatic Personality Inventory (UPI), workplace spirituality was assessed using the Spirituality of Work Scale (SWS), and workplace deviant behavior was assessed using the Workplace Deviant Behavior Inventory (WDB). Confirmatory factor analysis (CFA) and structural equation modeling (SEM) were used to analyze data from N = 311 healthcare professionals working in an Islamic hospital in Palembang, South Sumatera, Indonesia. Workplace spirituality, according to the study's findings, acted as a mediator between Islamic personality and deviant behavior at work, having a negative indirect influence. In conclusion, workplace spirituality and Islamic personality were the most significant influences on deviant behavior. In addition, coaching programs to improve collaboration and group cohesiveness among healthcare professionals should be implemented, as well as corrective teamwork training, to guarantee high productivity.